The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/hep.20584
|View full text |Cite
|
Sign up to set email alerts
|

Variceal ligation plus nadolol compared with ligation for prophylaxis of variceal rebleeding: A multicenter trial

Abstract: and the EVL Study Group ␤-Blockers and endoscopic variceal ligation (EVL) have proven to be valuable methods in the prevention of variceal rebleeding. The aim of this study was to compare the efficacy of EVL combined with nadolol versus EVL alone as secondary prophylaxis for variceal bleeding. Patients admitted for acute variceal bleeding were treated during emergency endoscopy with EVL or sclerotherapy and received somatostatin for 5 days. At that point, patients were randomized to receive EVL plus nadolol or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
130
1
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(142 citation statements)
references
References 37 publications
4
130
1
7
Order By: Relevance
“…Two randomized trials demonstrate the superiority of combined therapy versus EVL alone. 123,124 Rebleeding rates in these 2 trials were 23% and 14%, respectively, for EVL plus nadolol compared to 47% and 38% for EVL alone. These results support the use of combination therapy to prevent rebleeding, even though a recent consensus conference recommended EVL or ␤-blocker ϩ nitrates as first-line therapy in treatmentnaïve patients.…”
Section: E Patients With Cirrhosis Who Have Recovered From Acute Varmentioning
confidence: 96%
“…Two randomized trials demonstrate the superiority of combined therapy versus EVL alone. 123,124 Rebleeding rates in these 2 trials were 23% and 14%, respectively, for EVL plus nadolol compared to 47% and 38% for EVL alone. These results support the use of combination therapy to prevent rebleeding, even though a recent consensus conference recommended EVL or ␤-blocker ϩ nitrates as first-line therapy in treatmentnaïve patients.…”
Section: E Patients With Cirrhosis Who Have Recovered From Acute Varmentioning
confidence: 96%
“…Enhanced efficacy by use of beta blockers combined with EVL has been well established in the secondary prophylaxis of variceal bleeding. 16,25 It is still unknown whether a combination of EVL and beta blockers in the primary prophylaxis of variceal bleeding can be similarly effective.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of data on the incidence of bleeding from such ulcers. Results from secondary prophylaxis trials for esophageal variceal bleed showed that bleeding from postbanding ulcers is relatively uncommon [11,12]. A study by de la Peña et al (n = 80) [11] showed that four of the 20 rebleeding cases were due to bleeding esophageal ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Results from secondary prophylaxis trials for esophageal variceal bleed showed that bleeding from postbanding ulcers is relatively uncommon [11,12]. A study by de la Peña et al (n = 80) [11] showed that four of the 20 rebleeding cases were due to bleeding esophageal ulcers. Similarly, a study by Lo et al (n = 122) [12] showed that seven of the 71 rebleeding episodes were due to esophageal ulcers.…”
Section: Discussionmentioning
confidence: 99%